Upaya Meningkatkan Profesionalisme Guru di SD Inpres Bere-Bere Kecil Kecamatan Morotai Jaya - Yotam Kasene (Jurnal Ilmiah Wahana Pendidikan, 2020)
The aim of this research is to know the improvement of teachers' professional competence in SD Inpres Bere-Bere Kecil. Factors that become obstacles for teachers in improving teacher professional competence in SD Inpres Bere-Bere Kecil. This type of research used in this research is qualitative research. The results in this study are, Principals in improving teacher pedagodic competence by providing direct guidance and supervision of teachers related to the process of implementing learning in the classroom. principals in improving teacher competence by setting good examples for teachers. The principal always supervises the teacher both in the classroom and outside the classroom. If there is a teacher's behavior that is contrary to the norms of the teacher's personality competence, then the school principal provides guidance in the form of an individual approach and gives a direct warning to the teacher. in increasing the professional competence of teachers, by conducting coaching and including teachers in training activities, seminars, workshops, and KKG, to expand teacher knowledge and gain new knowledge.